An echocardiographic study of right ventricular adaptation to physical exercise in elite male orienteers - Henriksen, E.; Kangro, T.; Jonason, T.; Landelius, J.; Hedberg, P.; Ekstrand, P.; Ringqvist, I. (Clinical Physiology and Functional Imaging, 1998)
Considerably more publications appear on left ventricular morphology than on the right ventricle. The reasons for this imbalance are related to the complex shape of the right ventricular cavity and its position beneath the sternum, making imaging, measurement and functional assessment much more complex than the left ventricular chamber. Little attention has been directed towards right ventricular changes because of training, therefore the present study was designed to assess right ventricular changes due to extensive training by comparing cavity and wall dimensions in 29 sedentary men (mean age 23 years) and 82 elite male orienteers (mean age 22 years). The elite orienteers had on average significantly larger right ventricular outflow (10%) and right ventricular inflow (12%) tract 2 and 3 dimensions. The right ventricular wall measurements were on average 13% larger in the orienteers than the sedentary men. The right ventricular enlargement in endurance athletes probably reflects the increased haemodynamic loading that is caused by prolonged and extensive physical training. The thicker right ventricular wall in endurance athletes increases the contractile reserve and decreases wall stress in the right ventricle.